Distribution Pattern of Some Heavy Metals in the Soil of Silghat Region of Assam (India), Influenced by Jute Mill Solid Waste. (26th August 2012) - Bora, Pronil Kumar; Chetry, Sanjib; Sharma, Dharmendra Kumar; Saikia, Palash Moni
Abstract : Physico-chemical Analysis of the soil of Silghat region of Nagoan district of Assam, India was carried out to assess the possible effect of jute mill solid waste in the distribution pattern of some heavy metals. Soil samples were collected from ten different locations of the dumping site of the mill and their physico-chemical parameters were analyzed. Scanning Electron Microscopy-Energy Dispersive X-ray analysis (SEM-EDX) and Inductively coupled Plasma-Optical Emission Spectrometer (ICP-OES) analysis of the samples shows that soil of the dumping sites is highly enriched with heavy metals. The concentration of Fe, Cu, Zn and Pb in the contaminated soil was found to be very much higher than both the continental crust and world rock average values. Correlation studies indicate strong positive correlation between organic carbon content (C org ) with all the metals investigated. pH has negative correlation while positive correlation was observed for electrical conductivity with all the metals. Extent of metal contamination was assessed by determining contamination degree (CD) and pollution load index (PLI).